Building reinforced high-ductility concrete material
By adding calcium aluminate cement, silica fume and other components to the concrete, the microstructure and interface bonding performance of the material are optimized, and the problems of slow growth in early strength, poor interface bonding performance and insufficient ductility are solved, and higher early strength and ductility are achieved, which is suitable for building reinforcement and restoration.
Patent Information
- Application Number
- CN202510040571.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional concrete materials have slow growth in early strength, poor interface bonding performance and insufficient ductility, which leads to brittle damage prone to dynamic loads or earthquake conditions, and cannot meet the needs of modern engineering for earthquake resistance or flexible repair.
By adding calcium aluminate cement, silica fume, PVA fiber, magnesium-based expansion agent and cold phosphate binder to the concrete material, the microstructure and interface bonding performance of the material is optimized, and early strength and ductility are improved.
It has achieved significant improvement in early strength, improved interface bonding performance and enhanced ductility of concrete, and can show higher toughness and crack resistance under dynamic load conditions, meeting the needs of building reinforcement and restoration.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a building reinforcement type high-ductility concrete material. Background Art
[0002] In construction projects, concrete is widely used due to its high strength, good durability and strong construction adaptability. However, traditional concrete materials based on ordinary Portland cement have many shortcomings in actual use: The hardening process of ordinary Portland cement relies on the hydration reaction of silicate minerals, but the reaction rate is slow, especially in low temperature or low humidity environments. The early strength increases slowly and cannot meet the needs of emergency reinforcement or rapid repair projects. Although the existing technology improves the early strength by adding early strength agents, adjusting the mix ratio, etc., these methods often fail to take into account the long-term performance of the material, which may lead to insufficient strength or cracking of the material in the later stage. In addition, the interface bonding performance of traditional reinforced concrete is poor, and the junction of new and old concrete becomes a weak link, which is prone to interface failure due to stress concentration, thereby reducing the reinforcement effect; Moreover, existing concrete is essentially a brittle material with a tensile strength far lower than its compressive strength, making it difficult to achieve effective energy dissipation. As a result, the improvement in ductility is limited. Especially under dynamic loads or earthquakes, traditional concrete suffers from a significant lack of ductility, manifesting as brittle failure, which cannot meet the needs of modern engineering for earthquake resistance or flexible repair. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a building reinforcement type high-ductility concrete material, which solves the problems of slow early strength growth, poor interface bonding performance, insufficient ductility, and brittle failure under dynamic load or earthquake conditions of traditional concrete.
[0004] To achieve the above objectives, the present invention is implemented through the following technical solutions: A building reinforcement type high ductility concrete material, comprising the following components in mass fraction ratio: Ordinary Portland cement: 40-50 parts; Calcium aluminate cement: 10-15 parts; Silica fume: 5-10 parts; Fine aggregate: 20-30 parts; PVA fiber: 0.2-1.0 parts; Magnesium-based expansion agent: 3-8 parts; Cold phosphate binder: 2-5 parts; Water reducing agent: 0.5-1.0 part.
[0005] Preferably, the particle diameter of the calcium aluminate cement is 20-50 μm, and the particle diameter of the silica fume is 0.1-0.5 μm.
[0006] Among them, ordinary Portland cement is the basic cementitious material of concrete. Its main component, calcium silicate, generates CSH gel and calcium hydroxide (Ca(OH)2) through hydration reaction, providing basic strength and bonding properties. Calcium aluminate cement reacts with silica fume. Silica fume (ultrafine powder, particle diameter is 0.1-0.5μm) reacts with Ca(OH)2 through the volcanic ash effect to generate more CSH gel, while the aluminate in calcium aluminate cement (particle diameter is 20-50μm) reacts with sulfate ions to form calcium aluminate (AFt). This microstructure optimization significantly improves the early strength, density and durability of the material.
[0007] Preferably, the fine aggregate includes one or more of natural river sand, machine-made sand or quartz sand.
[0008] Aggregates provide concrete skeleton support, fill the pores in concrete, reduce the amount of slurry, and enhance its volume stability. Using high-hardness materials such as quartz sand can further improve the wear resistance and strength of the material; machine-made sand has certain edges and corners, which can improve the interface bonding performance of the cement matrix; natural river sand improves the working performance of concrete due to its smooth particles.
[0009] Preferably, the PVA fiber has a diameter of 15 to 25 μm and a length of 8 to 10 mm.
[0010] Among them, PVA fibers (diameter of 15-25μm, length of 8-10mm) are evenly dispersed in the concrete matrix. Through their high strength and high toughness characteristics, they can bridge microcracks under external forces and inhibit further expansion of cracks, thus giving the material a significant toughening effect. At the same time, the multi-crack cracking mechanism of PVA fibers can effectively delay the brittle failure behavior of concrete and significantly improve the ductility and crack resistance of concrete.
[0011] Preferably, the magnesium-based expansion agent includes one or more of magnesium oxide, magnesium hydroxide or magnesium carbonate.
[0012] Among them, magnesium-based expansive agents release expansion stress through hydration reaction to compensate for the shrinkage effect of concrete during the hardening process. Magnesium oxide slowly hydrates to form magnesium hydroxide, providing a long-lasting expansion effect and reducing later cracks; magnesium hydroxide and magnesium carbonate can produce early expansion, filling micro-cracks and pores in concrete, further improving its crack resistance and impermeability.
[0013] Preferably, the cold phosphate binder includes one or more of ammonium dihydrogen phosphate, sodium dihydrogen phosphate or potassium dihydrogen phosphate.
[0014] Among them, cold phosphate binder reacts with metal oxides to form insoluble phosphate gel (such as magnesium phosphate or zinc phosphate). This dense chemical combination not only improves the concrete's resistance to chemical corrosion, but also significantly improves the bonding strength between new and old concrete by enhancing the interfacial bonding force. It is particularly suitable for building reinforcement projects.
[0015] Preferably, the water reducer includes one or more of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer or an aliphatic water reducer; The naphthalene series water reducer includes: one of polynaphthalene sulfonate water reducer, sulfonated naphthalene anthracene formaldehyde condensate water reducer or β-naphthalene sulfonic acid formaldehyde condensate water reducer; The polycarboxylic acid water reducer includes: one of a polyether polycarboxylic acid water reducer, a hydroxyl polycarboxylic acid water reducer or a carboxymethyl polycarboxylic acid water reducer; The aliphatic water reducer includes: one of a lignin sulfonate water reducer, an aliphatic sulfonate water reducer or an aliphatic carboxylate water reducer.
[0016] Among them, naphthalene-based water reducers (such as polynaphthalene sulfonate water reducers) disperse cement particles through electrostatic repulsion, significantly reducing the water demand of the mixture; Polycarboxylic acid-based water reducers (such as polyether polycarboxylic acid water reducers) provide higher water reduction rate and slump retention performance through the dual effects of electrostatics and steric hindrance, and are suitable for high-fluidity concrete; Aliphatic water reducers, such as lignin sulfonate water reducers, improve the workability of concrete by dispersing cement particles and providing lubrication, while also reducing costs.
[0017] A method for preparing a building reinforcement type high ductility concrete material comprises the following steps: (a): Raw material preparation Preparation of powder components: Weigh ordinary Portland cement, calcium aluminate cement, silica fume, fine aggregate, magnesium-based expansion agent, cold phosphate binder and water reducing agent according to the proportion; PVA fiber is packed separately: Weigh the PVA fibers according to the proportion and store them separately in sealed packages; Step (b): Powder mixing Coarse powder mix: Adding ordinary Portland cement, calcium aluminate cement and fine aggregate into a mixing device in proportion and performing rough mixing; Fine powder mixing: Add silica fume, magnesium-based expansion agent, cold phosphate binder and water reducer to the coarse mixture in sequence, and package after mixing; Step (c): On-site operation During construction, pour the powder and PVA fiber directly into the mixing equipment, add water in proportion, and mix evenly to form reinforced high-ductility concrete.
[0018] Preferably, in the coarse powder mixing of step (b), the mixing equipment comprises: Double helix cone mixer: stirring speed: 50-80rpm, stirring time: 2-3min; Horizontal ribbon mixer: stirring speed: 30-60rpm, stirring time: 3-4min; Vertical planetary mixer: stirring speed: stirring paddle 30-50rpm, stirring drum 5-15rpm, stirring time: 3-4min; In the fine powder mixture of step (b), silica fume, magnesium-based expansion agent, cold phosphate binder and water reducing agent are added, and the stirring is maintained at a rotation speed for 3 to 5 minutes.
[0019] Preferably, the ratio of adding water in step (c) is: powder: water = 100:35-45.
[0020] The present invention provides a building reinforcement type high ductility concrete material. It has the following beneficial effects: 1. In the present invention, calcium aluminate cement and silica fume react with each other to generate calcium sulfonite and (CSH) gel. The calcium sulfonite formed by the aluminate ions and sulfate ions of the calcium aluminate cement can quickly fill the pores and improve the early strength; the active silica in the silica fume reacts with calcium hydroxide to generate high-strength CSH gel, thereby further improving the durability and compressive properties of the concrete. At the same time, the silica fume also plays a micro-filling role, effectively reducing the porosity and enhancing the interfacial bonding performance. Compared with the inefficient reaction of the prior art that simply relies on the hydration products of ordinary silicate cement, the present invention achieves more efficient pore filling and structural optimization through the synergistic effect of calcium aluminate cement and silica fume, overcomes the technical bottlenecks of insufficient early strength and poor interfacial bonding of traditional reinforcement materials, and exhibits excellent reinforcement effects in building reinforcement and repair projects.
[0021] 2. In the process of crack expansion, the fiber bridging force of PVA fiber can effectively inhibit the further development of cracks. Due to its high tensile strength and chemical affinity, PVA fiber is tightly combined with the cement matrix, and can disperse the concentrated stress into multiple crack effects under load, thereby enhancing the crack resistance and ductility of the material, and making it show a significant toughness advantage in a dynamic load environment.
[0022] 3. The present invention introduces a magnesium-based expansion agent to compensate for the volume shrinkage during the hardening process of concrete, and uses magnesium oxide to slowly hydrate to generate magnesium hydroxide, releasing micro-expansion stress to offset the shrinkage stress of concrete in a dry environment, thereby reducing the formation of shrinkage cracks. Compared with the disadvantage of traditional technology that relies on low shrinkage formulas and cannot completely avoid cracks, the present invention achieves a continuous shrinkage compensation effect while maintaining structural stability in the later stage of material hardening. Solve the long-term hidden danger of crack expansion due to volume deformation. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.
[0025] Example 1 Material ratio: Ordinary Portland cement: 45 parts; Calcium aluminate cement: 15 parts; Silica fume: 7 parts; Fine aggregate (quartz sand): 25 parts; PVA fiber: 0.8 parts; Magnesium-based expansion agent: 6 parts; Cold phosphate adhesive: 4 parts; Water reducing agent (polycarboxylic acid series): 0.8 parts.
[0026] step: Raw material preparation: weigh ordinary Portland cement, calcium aluminate cement, silica fume, quartz sand and other components according to the ratio; PVA fiber is packaged separately to avoid mixing with the powder.
[0027] Coarse powder mixing: ordinary Portland cement, calcium aluminate cement and quartz sand are placed in a horizontal ribbon mixer at a stirring speed of 50 rpm for 3 minutes.
[0028] Fine powder mixing: gradually add silica fume, magnesium-based expansion agent, cold phosphate binder and water reducer, maintain the stirring speed at 50 rpm, stir for 4 minutes and then package.
[0029] On-site construction: Pour the powder and PVA fiber into a mixer, add water at a ratio of powder: water = 100:38, stir for 5 minutes and then use.
[0030] Example 2 Material ratio: Ordinary Portland cement: 50 parts; Calcium aluminate cement: 12 parts; Silica fume: 10 parts; Fine aggregate (machine-made sand): 30 parts; PVA fiber: 0.5 parts; Magnesium-based expansion agent: 8 parts; Cold phosphate adhesive: 3 parts; Water reducing agent (aliphatic): 0.6 parts.
[0031] step: Raw material preparation: Weigh cement, calcium aluminate cement, silica fume and other components in proportion; sieve the machine-made sand to remove impurities; and package the PVA fibers independently.
[0032] Coarse powder mixing: Add cement, calcium aluminate cement and machine-made sand into a double-screw cone mixer at a speed of 60 rpm and mix for 2 minutes.
[0033] Fine powder mixing: Add silica fume, magnesium-based expansion agent, cold phosphate binder and aliphatic water reducer and stir for 3 minutes.
[0034] On-site construction: Mix the powder with PVA fiber, add water at a ratio of 100:40, stir evenly and pour into shape.
[0035] Example 3 Material ratio: Ordinary Portland cement: 40 parts; Calcium aluminate cement: 13 parts; Silica fume: 6 parts; Fine aggregate (natural river sand): 28 parts; PVA fiber: 1.0 part; Magnesium-based expansion agent: 5 parts; Cold phosphate adhesive: 5 parts; Water reducing agent (naphthalene series): 1.0 part.
[0036] step: Raw material preparation: Ordinary Portland cement, calcium aluminate cement, and river sand are sieved to remove impurities; PVA fiber is stored separately.
[0037] Coarse powder mixing: cement, calcium aluminate cement and river sand are put into a vertical planetary mixer with the paddle speed at 40 rpm and the mixing drum at 10 rpm for 3 minutes.
[0038] Fine powder mixing: Add silica fume, magnesium-based expansion agent, cold phosphate binder and naphthalene-based water reducer in sequence, stir for 4 minutes and pack evenly.
[0039] On-site construction: Mix the powder and PVA fiber in proportion, add water (powder: water = 100:35), stir evenly and then repair the post-earthquake cracks in the concrete.
[0040] Example 4 Material ratio: Ordinary Portland cement: 48 parts; Calcium aluminate cement: 10 parts; Silica fume: 10 parts; Fine aggregate (quartz sand): 25 parts; PVA fiber: 0.4 parts; Magnesium-based expansion agent: 7 parts; Cold phosphate adhesive: 3 parts; Water reducing agent (polycarboxylic acid series): 0.7 parts.
[0041] step: Raw material preparation: weigh cement, calcium aluminate cement, and quartz sand according to the ratio; store PVA fiber separately for future use.
[0042] Coarse powder mixing: Add ordinary Portland cement, calcium aluminate cement and quartz sand into a horizontal ribbon mixer at a speed of 40 rpm and mix for 3 minutes.
[0043] Fine powder mixing: Add silica fume, magnesium-based expansion agent, cold phosphate binder and polycarboxylate water reducer, mix for 4 minutes and package into powder.
[0044] On-site construction: add water at a ratio of powder: water = 100:37, stir evenly and use it for pouring the reservoir waterproofing layer.
[0045] Example 5 Material ratio: Ordinary Portland cement: 45 parts; Calcium aluminate cement: 15 parts; Silica fume: 8 parts; Fine aggregate (machine-made sand): 30 parts; PVA fiber: 0.7 parts; Magnesium-based expansion agent: 5 parts; Cold phosphate adhesive: 4 parts; Water reducing agent (naphthalene): 0.9 parts step: Raw material preparation: calcium aluminate cement, machine-made sand screening, PVA fiber separate packaging.
[0046] Coarse powder mixing: put cement and machine-made sand into a double-screw cone mixer at 60 rpm and stir for 2 minutes.
[0047] Fine powder mixing: Add silica fume, magnesium-based expansion agent, cold phosphate binder and water reducer in sequence, stir for 3 minutes and then package.
[0048] On-site construction: add water at a ratio of 100:40 and mix evenly before use for emergency road repairs Comparative Example A: Omitting calcium aluminate cement and relying entirely on ordinary Portland cement Ratio: Ordinary Portland cement: 55 parts; Silica fume: 7 parts; Fine aggregate (quartz sand): 25 parts; PVA fiber: 0.8 parts; Magnesium-based expansion agent: 6 parts; Cold phosphate adhesive: 4 parts; Water reducing agent (polycarboxylic acid series): 0.8 parts.
[0049] Specific preparation process: Raw material preparation: weigh ordinary Portland cement, silica fume, quartz sand and other components according to the above proportions; PVA fiber is packaged separately to avoid mixing with the powder.
[0050] Coarse powder mixing: Add ordinary Portland cement and quartz sand into a horizontal ribbon mixer, stir at 50 rpm and mix for 3 minutes.
[0051] Fine powder mixing: gradually add silica fume, magnesium-based expansion agent, cold phosphate binder and water reducer, maintain the speed and stir for 4 minutes before packaging.
[0052] Construction mixing: Pour the powder and PVA fiber into the mixing equipment, add water at the ratio of powder: water = 100:38, stir for 5 minutes and then apply.
[0053] Comparative Example B: Reduce the amount of magnesium-based expansion agent Ratio: Ordinary Portland cement: 50 parts; Calcium aluminate cement: 12 parts; Silica fume: 10 parts; Fine aggregate (machine-made sand): 30 parts; PVA fiber: 0.5 parts; Magnesium-based expansion agent: 1 part; Cold phosphate adhesive: 3 parts; Water reducing agent (aliphatic): 0.6 parts.
[0054] Specific preparation process: Raw material preparation: weigh ordinary Portland cement, calcium aluminate cement, machine-made sand, silica fume and other components; PVA fiber is packaged separately and set aside.
[0055] Coarse powder mixing: put ordinary Portland cement, calcium aluminate cement and machine-made sand into a double-screw cone mixer at a speed of 60 rpm and mix for 2 minutes.
[0056] Fine powder mixing: gradually add silica fume, magnesium-based expansion agent, cold phosphate binder and aliphatic water reducer, mix for 3 minutes and then package.
[0057] Construction mixing: Mix the powder with PVA fiber, add water at a ratio of powder to water = 100:40, stir evenly and use for construction.
[0058] Comparative Example C: Silica fume is omitted, and only ordinary silicate cement and calcium aluminate cement are retained Ratio: Ordinary Portland cement: 40 parts; Calcium aluminate cement: 13 parts; Fine aggregate (natural river sand): 28 parts; PVA fiber: 1.0 part; Magnesium-based expansion agent: 5 parts; Cold phosphate adhesive: 5 parts; Water reducing agent (naphthalene series): 1.0 part.
[0059] Specific preparation process: Raw material preparation: weigh ordinary Portland cement, calcium aluminate cement, and natural river sand; store PVA fiber separately to avoid mixing with the powder.
[0060] Coarse powder mixing: Add ordinary Portland cement, calcium aluminate cement and natural river sand into a vertical planetary mixer, with the paddle speed at 40 rpm and the mixing drum speed at 10 rpm, and mix for 3 minutes.
[0061] Fine powder mixing: gradually add magnesium-based expansion agent, cold phosphate binder and naphthalene-based water reducer, stir for 4 minutes and pack evenly.
[0062] Construction mixing: Add water to the powder at a ratio of 100:35, add PVA fiber and mix evenly, and use it to repair concrete cracks.
[0063] Comparative Example D: No cold phosphate binder was used Ratio: Ordinary Portland cement: 48 parts; Calcium aluminate cement: 10 parts; Silica fume: 10 parts; Fine aggregate (quartz sand): 25 parts; PVA fiber: 0.4 parts; Magnesium-based expansion agent: 7 parts; Water reducing agent (polycarboxylic acid series): 0.7 parts.
[0064] Specific preparation process: Raw material preparation: weigh ordinary Portland cement, calcium aluminate cement, quartz sand, silica fume and other components; store PVA fiber separately for future use.
[0065] Coarse powder mixing: Add ordinary Portland cement, calcium aluminate cement and quartz sand into a horizontal ribbon mixer at a speed of 50 rpm and mix for 3 minutes.
[0066] Fine powder mixing: Add silica fume, magnesium-based expansion agent and polycarboxylic acid water reducer in sequence, stir for 4 minutes and then package.
[0067] Construction mixing: Mix the powder and PVA fiber evenly in the ratio of powder: water = 100:37 and then pour.
[0068] Comparative Example E: No PVA fiber used Ratio: Ordinary Portland cement: 45 parts; Calcium aluminate cement: 15 parts; Silica fume: 8 parts; Fine aggregate (machine-made sand): 30 parts; Magnesium-based expansion agent: 5 parts; Cold phosphate adhesive: 4 parts; Water reducing agent (naphthalene series): 0.9 parts.
[0069] Specific preparation process: Raw material preparation: weigh ordinary Portland cement, calcium aluminate cement, silica fume, machine-made sand and other components.
[0070] Coarse powder mixing: ordinary Portland cement, calcium aluminate cement and machine-made sand are put into a double-screw cone mixer at a speed of 60 rpm and mixed for 2 minutes.
[0071] Fine powder mixing: gradually add silica fume, magnesium-based expansion agent, cold phosphate binder and naphthalene-based water reducer, stir for 3 minutes and then package.
[0072] Construction mixing: Add water to the powder at a ratio of 100:40 and mix evenly before pouring.
[0073] Experiment 1: Early strength comparison experiment Experimental Description Purpose: The effect of the synergistic effect of calcium aluminate cement and silica fume on the early strength of concrete was verified, and by comparing Example 1 with Comparative Example A, the advantages of the present invention in reinforcement performance were highlighted.
[0074] Experimental steps: 1. Material preparation: Example 1: Powder was prepared according to the ratio of 45 parts of ordinary Portland cement, 15 parts of calcium aluminate cement, 7 parts of silica fume, 25 parts of quartz sand, 0.8 parts of PVA fiber, 6 parts of magnesium-based expansion agent, 4 parts of cold phosphate binder and 0.8 parts of water reducer. Water was added at a ratio of powder: water = 100:38, and the test piece was prepared after stirring evenly.
[0075] Comparative Example A: Powder was prepared according to the ratio of 55 parts of ordinary Portland cement (cement without calcium aluminate), 7 parts of silica fume, 25 parts of quartz sand, 0.8 parts of PVA fiber, 6 parts of magnesium-based expansion agent, 4 parts of cold phosphate binder and 0.8 parts of water reducer. Water was added in the ratio of powder: water = 100:38 and stirred evenly to prepare the test piece.
[0076] 2. Specimen forming: Prepare cubic specimens with a side length of 100 mm and compact them according to the standard vibration to ensure that the concrete slurry is evenly distributed and the surface is flat. Make at least 6 specimens in each group.
[0077] 3. Maintenance conditions: Place the specimens in a standard curing room and control the temperature to 20±2℃ and the relative humidity to above 95%.
[0078] 4. Compressive strength test: The compressive strength of the specimens was tested at the ages of 1 day, 3 days and 7 days using a pressure testing machine (loading rate of 0.5 MPa / s), the maximum load at failure was recorded and the compressive strength was calculated.
[0079] Experimental data Table 1: Comparative data of early compressive strength of Example 1 and Comparative Example A Experimental Summary The synergistic effect of calcium aluminate cement and silica fume shows outstanding effects in early strength. Calcium aluminate cement quickly generates calcium sulfonate during the hydration reaction. This dense crystal effectively fills the pores of concrete. Calcium sulfonate not only enhances the initial strength, but also improves the bonding force between new and old particles through interface optimization. When comparative example A lacks calcium aluminate cement, the pore filling efficiency decreases significantly, resulting in a significant lag in early strength. The difference in 1-day strength in the data already illustrates this problem.
[0080] The introduction of silica fume further strengthens the synergistic effect. The active silica in silica fume reacts with the calcium hydroxide generated by hydration to generate a large amount of CSH gel. This gel has extremely high strength and adhesion, and significantly improves the overall performance of the matrix structure. Although silica fume is also added to Comparative Example A, due to the lack of rapid reaction of calcium aluminate cement, the utilization efficiency of calcium hydroxide is insufficient, resulting in limited CSH gel generation and slow improvement in compressive strength.
[0081] It can be seen from the experiment that the strength difference between 1 day and 3 days is the largest. This fully demonstrates the contribution of the rapid hardening characteristics of calcium aluminate cement to early performance. The generation rate of calcium aluminate is significantly better than the hydration process of ordinary Portland cement, and this effect is particularly important in bridge and road repair projects that require rapid reinforcement. Although the strength of ordinary Portland cement has increased at the age of 7 days, it still has not reached the level of Example 1, reflecting the essential difference between the two materials in the microscopic reaction mechanism.
[0082] Experiment 2: Comparative experiment on crack resistance Experimental Description Purpose: The effect of PVA fiber on the crack resistance of concrete was verified by comparing Example 3 (containing PVA fiber) with Comparative Example E (without PVA fiber) to evaluate the inhibitory effect of fiber on crack propagation and load dispersion performance.
[0083] Experimental steps: 1. Material preparation: Example 3 (containing PVA fiber): Powder was prepared according to the ratio of 40 parts of ordinary Portland cement, 13 parts of calcium aluminate cement, 6 parts of silica fume, 28 parts of natural river sand, 1.0 part of PVA fiber, 5 parts of magnesium-based expansion agent, 5 parts of cold phosphate binder and 1.0 part of water reducer. The powder and water were mixed evenly at a ratio of powder: water = 100:35, and PVA fiber was added, and stirring was continued until the fiber was evenly distributed.
[0084] Comparative Example E (without PVA fiber): 1.0 part of PVA fiber was omitted from the ratio, and the other components were the same as those in Example 3. The powder and water were stirred evenly in a ratio of 100:35.
[0085] 2. Specimen forming: Prepare 300×100×50mm prism specimens, with no less than 3 specimens in each group to ensure the reliability of the results. Vibrate and compact the specimens to make the surface smooth and flat.
[0086] 3. Maintenance conditions: The specimens were cured in a standard curing room for 28 days (temperature 20±2℃, relative humidity above 95%).
[0087] 4. Crack width test: The specimen was mounted on a three-point bending tester (span 250 mm), and the load was applied gradually. The load at the onset of the crack (initial crack load), as well as the load and maximum crack width when the crack developed to a width of 1.0 mm were recorded.
[0088] 5. Experimental indicators: First crack load (load when crack first occurs); Maximum crack width (maximum crack width when loaded to specimen failure); Crack development load (load when the crack width reaches 1.0 mm).
[0089] Table 2: Comparative data of crack resistance of Example 3 and Comparative Example E Experimental Summary PVA fibers play a significant role in the generation and expansion of cracks. In the early stage, a bridging effect is formed between the fiber and the matrix, which effectively disperses the stress. When the crack is first generated, the initial crack load of Example 3 is more than 30% higher than that of Comparative Example E, indicating that the fiber can delay the occurrence of cracks. Due to the lack of fiber effect, the cracks in Comparative Example E tend to appear quickly at the stress concentration point, showing a lower initial crack load.
[0090] During the crack expansion stage, PVA fibers further demonstrated their crack resistance. The fibers continued to stretch at the crack tip and prevented the crack from expanding, so the load was redistributed and the growth of the crack width was significantly suppressed. The load of Example 3 when the crack width reached 1.0 mm was significantly higher than that of Comparative Example E, and the maximum crack width was also significantly smaller. The crack expansion of Comparative Example E was relatively rapid, and the crack width was nearly twice that of Example 3 when the specimen was finally destroyed, indicating that concrete without fibers could not prevent crack penetration.
[0091] In terms of the mechanism for improving crack resistance, the high strength and high modulus of PVA fibers are the key. The fibers absorb the energy of crack development by stretching, converting concentrated stress into distributed stress, and forming multiple bridge points on both sides of the cracks, making the cracks tend to a multi-crack mode, avoiding penetrating damage. In comparative example E, the cracks lost the restraining effect of the fibers, resulting in a single crack that rapidly expanded and penetrated, and the concrete failure showed brittle characteristics. Therefore, the results of this experiment fully prove that PVA fibers have a significant effect on enhancing the crack resistance of concrete.
[0092] Experiment 3: Volume stability comparison experiment Experimental Description Purpose: The improvement effect of the magnesium-based expansive agent on the volume stability of the concrete hardening process was verified, and the influence of the amount of the expansive agent on the shrinkage and expansion properties was evaluated by comparing Example 2 (8 parts of magnesium-based expansive agent) and Comparative Example B (1 part of magnesium-based expansive agent).
[0093] Experimental steps: 1. Material preparation: Example 2: Prepare powder according to the ratio of 50 parts of ordinary Portland cement, 12 parts of calcium aluminate cement, 10 parts of silica fume, 30 parts of machine-made sand, 0.5 parts of PVA fiber, 8 parts of magnesium-based expansion agent, 3 parts of cold phosphate binder, and 0.6 parts of aliphatic water reducer. Mix evenly at a ratio of powder: water = 100:40 and then form.
[0094] Comparative Example B: The magnesium-based expansion agent is reduced to 1 part, and the proportions of the other components are the same as those of Example 2. The powder is stirred evenly at a ratio of powder to water = 100:40 and then formed.
[0095] 2. Specimen forming: Prepare prismatic specimens of 100×100×400mm, with no less than 3 specimens in each group. Vibrate and compact them to ensure that the surface of the specimens is flat and free of obvious bubbles or cracks.
[0096] 3. Maintenance conditions: The specimens were placed under standard humidity conditions (temperature 20±2°C, relative humidity 95%), and the length change rate was tested at 7 days and 28 days.
[0097] 4. Length change rate test: Use a length change meter to measure the change in length of the specimen during the hardening process, and record the initial length and the length at each age.
[0098] Calculate the length change rate formula:
[0099] 5. Experimental indicators: The length change rate at the age of 7 days and 28 days was tested to reflect the early expansion capacity and long-term volume stability of concrete, respectively.
[0100] Table 3: Comparative data of concrete volume stability of Example 2 and Comparative Example B Experimental Summary Experimental data show that magnesium-based expansive agents have a significant effect on the volume stability and ductility of concrete. The length change rate of Example 2 (8 parts of magnesium-based expansive agent) at 7 days of age is positive (+0.025~+0.030%), indicating that the expansive agent releases expansion stress during the early hydration process, effectively offsetting the shrinkage during the hardening process of concrete. It not only prevents the generation of microcracks, but also provides a good foundation for ductility. In contrast, Comparative Example B (1 part of magnesium-based expansive agent) showed significant volume shrinkage (-0.019%~-0.022%) at 7 days of age, and cracks were easily formed in a concentrated manner, indicating that its ductility was poor.
[0101] The data at 28 days further illustrate the key role of the expansion agent in long-term volume stability and ductility. The length change rate of Example 2 tends to be stable (+0.010~+0.015%), and the expansion effect and the contraction effect achieve a dynamic balance. This state not only improves the material's crack resistance, but also provides a guarantee for the energy dissipation after the crack develops, reflecting good ductility. The specimen of comparative example B showed a larger volume shrinkage (-0.033%~-0.037%) at 28 days, resulting in the gradual expansion of internal microcracks. The specimen finally showed significant brittle characteristics, and the lack of ductility was obvious.
[0102] The mechanism of action of magnesium-based expansion agent is that slow hydration reaction generates magnesium hydroxide, releases expansion stress, and effectively resists shrinkage stress in the early stage of crack formation. Not only compensates for the shrinkage during hardening, but also improves the stress dissipation capacity of the material by the uniform distribution of expansion stress, so that the crack is delayed and prevented during expansion. Experimental results show that the expansion agent dosage of embodiment 2 is sufficient, and the expansion effect is stable and continuous, ensuring the crack control ability and ductility of concrete in long-term use. And in comparative example B, the expansion agent dosage is insufficient, and the expansion stress is weak, causing the micro cracks in the hardening process to fail to be compensated, and the concrete as a whole is unstable in volume and insufficient in ductility, which eventually leads to brittle failure.
[0103] The experimental results fully prove that the dosage of magnesium-based expansive agent directly determines the volume stability and ductility of concrete. Especially under large-volume concrete and dynamic load conditions, high-ductility materials significantly improve the concrete's resistance to crack expansion through the uniform release of expansion stress, providing a better solution for modern building reinforcement projects.
[0104] Experiment 4: Interface adhesion comparison experiment Experimental Description Purpose: The effect of the cold phosphate binder on improving the interfacial adhesion between new and old concrete was verified, and the performance improvement of the binder at the junction of new and old concrete was evaluated by comparing Example 4 (containing the cold phosphate binder) with Comparative Example D (without the cold phosphate binder).
[0105] Experimental steps: 1. Material preparation: Example 4: Powder was prepared according to the ratio of 48 parts of ordinary Portland cement, 10 parts of calcium aluminate cement, 10 parts of silica fume, 25 parts of quartz sand, 0.4 parts of PVA fiber, 7 parts of magnesium-based expansion agent, 3 parts of cold phosphate binder, and 0.7 parts of polycarboxylate water reducer. The powder was stirred evenly at a ratio of powder: water = 100:37.
[0106] Comparative Example D: No cold phosphate binder was added in the mix, and the remaining components were the same as those in Example 4. The powder was stirred evenly at a ratio of powder to water = 100:37.
[0107] 2. Specimen preparation: Apply a layer of newly prepared concrete (75mm thick) on the hardened 150×150×75mm old concrete block. Vibrate and compact it to ensure that there are no obvious gaps at the interface.
[0108] Prepare 3 groups of specimens (no less than 3 in each group) for comparison under different experimental conditions.
[0109] 3. Maintenance conditions: The specimens were cured for 28 days in a standard curing environment at 20±2℃ and humidity above 95%.
[0110] 4. Interface adhesion test: Use a tensile testing machine to gradually apply tension to the specimen until the interface is damaged, and record the failure load.
[0111] The interfacial bonding strength (unit: MPa) is calculated by the following formula:
[0112] in, is the bonding strength, is the maximum pull-out load, is the interface area (150×150mm²).
[0113] 5. Experimental indicators: Test the interface bonding strength to reflect the performance of the combination of new and old concrete.
[0114] Table 4: Comparative data of bonding strength between new and old concrete interface of Example 4 and Comparative Example D Experimental Summary Cold phosphate binder significantly improves the bonding strength of the interface between new and old concrete, and its mechanism of action is closely related to the chemical reaction of the binder. The phosphate component in the cold phosphate binder can quickly react with metal oxides (such as magnesium oxide in magnesium-based expansion agents) to form a dense phosphate gel. This gel not only forms a strong chemical bond at the interface between new and old concrete, but can also penetrate into tiny cracks and pores to further enhance the bonding force. In Comparative Example D, due to the lack of binder, the new and old interfaces are only physically bonded, so the strength is relatively low, which is manifested as early interface damage.
[0115] The experimental results show that the performance of cold phosphate adhesive is particularly outstanding at 28 days. The interface bonding strength of Example 4 is more than 60% higher than that of Comparative Example D. The failure form in the pull-out test is mainly internal failure of the concrete matrix, indicating that the interface itself has exceeded the strength of the matrix. In Comparative Example D, interface failure is the main form, and the pull-out load is lower than that of Example 4. This shows the limitations of traditional formulas in interface bonding performance.
[0116] The role of cold phosphate adhesive is not only reflected in the bond strength, but also improves durability by improving the microstructure of the interface transition zone (ITZ). Phosphate gel fills the pores and microcracks at the interface between the new and the old, reducing the stress concentration effect and making the interface denser. This effect is particularly important for reinforcement projects or repairing old concrete, effectively solving the problem of insufficient interface bonding of traditional materials and improving the overall structural performance.
[0117] Experiment 5: Comparative experiment on anti-seepage performance Experimental Description Purpose: The effect of silica fume on improving the anti-permeability of concrete was verified, and the filling effect and chemical activity of silica fume on the durability of concrete were evaluated by comparing Example 4 (containing silica fume) and Comparative Example C (without adding silica fume).
[0118] Experimental steps: 1. Material preparation: Example 4: Powder was prepared according to the ratio of 48 parts of ordinary Portland cement, 10 parts of calcium aluminate cement, 10 parts of silica fume, 25 parts of quartz sand, 0.4 parts of PVA fiber, 7 parts of magnesium-based expansion agent, 3 parts of cold phosphate binder and 0.7 parts of polycarboxylate water reducer. The powder and water were mixed evenly at a ratio of powder: water = 100:37 and then formed.
[0119] Comparative Example C: Silica fume is omitted from the ratio, and the other components are the same as those in Example 4. The mixture is stirred evenly at a ratio of powder: water = 100:37 and then formed.
[0120] 2. Specimen forming: Prepare cylindrical specimens with a height of 150 mm and a diameter of 100 mm, with no less than 3 specimens in each group. Use the vibration method to compact the specimens to ensure that there are no obvious bubbles and cracks.
[0121] 3. Maintenance conditions: The specimens were placed in a standard humidity environment (temperature 20±2°C, relative humidity above 95%) for curing for 28 days.
[0122] 4. Anti-seepage performance test: After the specimen is saturated with water, it is placed in a water pressure and impermeability tester. The initial water pressure is 0.5MPa. The water pressure is increased by 0.1MPa every 6 hours, and the maximum water pressure value at which leakage occurs is recorded.
[0123] 5. Experimental indicators: Test the maximum water pressure resistance as an indicator of concrete's water resistance performance.
[0124] Table 5: Comparative data of concrete impermeability performance of Example 4 and Comparative Example C Experimental Summary The introduction of silica fume significantly improves the impermeability of concrete, which is directly related to its chemical activity and micro-filling effect. The active silica in the silica fume reacts secondary with the calcium hydroxide generated during the hydration of the concrete to generate a large amount of CSH gel. This gel not only has extremely high strength, but also can fill the pores in the concrete, effectively reducing the porosity and making the material more compact. In the experiment, the maximum impermeability water pressure of Example 4 is more than 50% higher than that of Comparative Example C, indicating that the contribution of silica fume to the impermeability performance is significant.
[0125] At the microscopic level, the particle diameter of silica fume is extremely small (0.1-0.5 μm), which can deeply fill the capillary pores of concrete. This micro-filling effect significantly reduces the number and connectivity of water passage paths, greatly reducing the permeability of concrete. In comparative example C, due to the lack of filling effect of silica fume, the capillary pores were not fully blocked and the permeability was significantly enhanced. In the test of gradually increasing anti-seepage water pressure, the comparative example C specimen leaked at around 0.8 MPa, indicating that its water pressure resistance is limited.
[0126] From the perspective of long-term durability, the improvement of the anti-permeability of concrete by silica fume is also reflected in the reduction of internal erosion risks. The reduction of capillary pores not only prevents water penetration, but also significantly slows down the invasion rate of harmful ions, enhancing the material's resistance to chemical erosion. This is especially important for projects such as underground structures and water conservancy facilities that are in long-term contact with water environments. The experimental results fully show that the introduction of silica fume effectively makes up for the shortcomings of traditional concrete in anti-permeability and significantly improves the density and durability of the material.
[0127] Experiment 6: Rapid hardening performance comparison experiment Experimental Description Purpose: The effect of calcium aluminate cement on rapid hardening performance was verified by comparing Example 5 (containing calcium aluminate cement) with Comparative Example A (not containing calcium aluminate cement) to evaluate its effect on improving early strength development.
[0128] Experimental steps: 1. Material preparation: Example 5: Powder is prepared according to the ratio of 45 parts of ordinary Portland cement, 15 parts of calcium aluminate cement, 8 parts of silica fume, 30 parts of machine-made sand, 0.7 parts of PVA fiber, 5 parts of magnesium-based expansion agent, 4 parts of cold phosphate binder, and 0.9 parts of naphthalene-based water reducer. The powder and water are mixed evenly at a ratio of powder: water = 100:40.
[0129] Comparative Example A: Calcium aluminate cement is not included, the amount of ordinary Portland cement is increased to 55 parts, and the other components are the same as those in Example 5. Mix evenly at a ratio of powder: water = 100:40.
[0130] 2. Specimen forming: Prepare cubic specimens with a side length of 100 mm, vibrate and compact them, and make the surface flat. Each group of no less than 6 specimens will be used for strength tests at different ages.
[0131] 3. Maintenance conditions: The specimens were cured in a standard curing environment with a temperature of 20±2℃ and a relative humidity of 95% to different ages.
[0132] 4. Compressive strength test: The compressive strength of the specimens was tested at 3 hours, 6 hours and 1 day. The specimens were loaded using a pressure testing machine (loading rate 0.5 MPa / s), the maximum load at failure was recorded, and the compressive strength was calculated.
[0133] 5. Experimental indicators: Test the compressive strength at different ages and evaluate the rapid hardening performance of concrete.
[0134] Table 6: Comparative data of early compressive strength of Example 5 and Comparative Example A.
[0135] Experimental Summary As shown in Table 6, calcium aluminate cement has a positive effect on the rapid hardening of concrete. Since the calcium aluminate crystals generated by its hydration reaction have high strength, the early strength is greatly improved. At the age of 3 hours, the compressive strength of Example 5 is about twice that of Comparative Example A, indicating that the rapid reaction of calcium aluminate cement effectively compensates for the lack of initial strength development of ordinary Portland cement. Comparative Example A completely relies on the hydration process of Portland cement, and the generation rate of calcium aluminate and CSH gel is slow, and the early strength is obviously lagging behind.
[0136] At 6 hours, the strength of Example 5 continued to increase rapidly, and the abundant aluminate in the calcium aluminate cement reacted with sulfate ions to generate a large amount of calcium aluminate, further optimizing the microstructure of the concrete. This reaction not only filled the pores, but also formed a bridging effect at the microcracks, improving the overall density and compressive resistance. In Comparative Example A, due to the lack of the rapid hardening characteristics of calcium aluminate cement, its strength development was still slow and still could not catch up with Example 5.
[0137] At the age of 1 day, although the strength gap between Example 5 and Comparative Example A has narrowed, the former still maintains a clear advantage. The early reaction of calcium aluminate cement and the volcanic ash effect of silica fume work together to significantly improve the density and interfacial bonding performance of concrete. In contrast, since Comparative Example A completely relies on silicate cement, its early strength improvement is relatively limited. The experimental results fully prove that calcium aluminate cement not only provides high strength in the early stage by quickly generating calcium sulfoxide and CSH gel, but also optimizes the microstructure of concrete, fundamentally solving the problem of insufficient early strength of traditional silicate cement.
[0138] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A building reinforcement type high ductility concrete material, characterized in that: It includes the following components in proportion by weight: Ordinary Portland cement: 40-50 parts; Calcium aluminate cement: 10-15 parts; Silica fume: 5-10 parts; Fine aggregate: 20-30 parts; PVA fiber: 0.2-1.0 parts; Magnesium-based expansion agent: 3-8 parts; Cold phosphate binder: 2-5 parts; Water reducing agent: 0.5-1.0 part.
2. A building reinforcement type high ductility concrete material according to claim 1, characterized in that: The particle diameter of the calcium aluminate cement is 20-50 μm, and the particle diameter of the silica fume is 0.1-0.5 μm.
3. A building reinforcement high ductility concrete material according to claim 1, characterized in that: The fine aggregate includes one or more of natural river sand, machine-made sand or quartz sand.
4. A building reinforcement type high ductility concrete material according to claim 1, characterized in that: The PVA fiber has a diameter of 15 to 25 μm and a length of 8 to 10 mm.
5. A building reinforcement type high ductility concrete material according to claim 1, characterized in that: The magnesium-based expansion agent includes one or more of magnesium oxide, magnesium hydroxide or magnesium carbonate.
6. A building reinforcement high ductility concrete material according to claim 1, characterized in that: The cold phosphate binder includes one or more of ammonium dihydrogen phosphate, sodium dihydrogen phosphate or potassium dihydrogen phosphate.
7. A building reinforcement high ductility concrete material according to claim 1, characterized in that: The water reducer includes one or more of a naphthalene water reducer, a polycarboxylic acid water reducer or an aliphatic water reducer; The naphthalene series water reducer includes: one of polynaphthalene sulfonate water reducer, sulfonated naphthalene anthracene formaldehyde condensate water reducer or β-naphthalene sulfonic acid formaldehyde condensate water reducer; The polycarboxylic acid water reducer includes: one of a polyether polycarboxylic acid water reducer, a hydroxyl polycarboxylic acid water reducer or a carboxymethyl polycarboxylic acid water reducer; The aliphatic water reducer includes: one of a lignin sulfonate water reducer, an aliphatic sulfonate water reducer or an aliphatic carboxylate water reducer.
8. A method for preparing a building reinforced high-ductility concrete material, based on the building reinforced high-ductility concrete material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (a): Raw material preparation Preparation of powder components: Weigh ordinary Portland cement, calcium aluminate cement, silica fume, fine aggregate, magnesium-based expansion agent, cold phosphate binder and water reducing agent according to the proportion; PVA fiber is packed separately: Weigh the PVA fibers according to the proportion and store them separately in sealed packages; Step (b): Powder mixing Coarse powder mix: Adding ordinary Portland cement, calcium aluminate cement and fine aggregate into a mixing device in proportion and performing rough mixing; Fine powder mixing: Add silica fume, magnesium-based expansion agent, cold phosphate binder and water reducer to the coarse mixture in sequence, and package after mixing; Step (c): On-site operation During construction, pour the powder and PVA fiber directly into the mixing equipment, add water in proportion, and mix evenly to form reinforced high-ductility concrete.
9. The method for preparing a building reinforcement type high ductility concrete material according to claim 8, characterized in that: In the coarse powder mixing of step (b), the mixing equipment comprises: Double helix cone mixer: stirring speed: 50-80rpm, stirring time: 2-3min; Horizontal ribbon mixer: stirring speed: 30-60rpm, stirring time: 3-4min; Vertical planetary mixer: stirring speed: stirring paddle 30-50rpm, stirring drum 5-15rpm, stirring time: 3-4min; In the fine powder mixture of step (b), silica fume, magnesium-based expansion agent, cold phosphate binder and water reducing agent are added, and the stirring is maintained at a rotation speed for 3 to 5 minutes.
10. The method for preparing a building reinforcement high ductility concrete material according to claim 8, characterized in that: The ratio of adding water in step (c) is: powder: water = 100:35-45.